Unusual Case of Metastatic Gastrointestinal Adenocarcinoma to the Cervical Spine without a Detectable Primary Source in a Patient with Acquired Immunodeficiency Syndrome: A Case Report. (9th October 2012) - Kaloostian, Paul E.; Barry, Marc; Harrington, James Fred
Abstract : The authors report a case of metastatic gastrointestinal adenocarcinoma to the cervical spine in a patient with acquired immunodeficiency syndrome (AIDS) being treated with antiretroviral therapy. The source of this tumor could not be identified despite a thorough evaluation. A 49-year-old male being treated for AIDS presents with worsening neck pain and left distal arm weakness. MRI demonstrated an erosive mass within the cervical four vertebral body extending through the pedicle on the left side. Patient underwent needle biopsy followed by combined anterior and posterior fusion procedures. Pathology demonstrated metastatic gastrointestinal adenocarcinoma without known primary origin. He is currently undergoing palliative radiotherapy. This is an unusual case of metastatic gastrointestinal adenocarcinoma to the cervical spine. This should be included on the differential diagnosis of spinal lesions in this patient population and may represent a unique tumor in patients with HIV/AIDS who are on immunosuppressive therapy.